On Univalence Criteria for a General Integral Operator - Vasile Marius Macarie; Daniel Breaz (Journal of Function Spaces and Applications)
We consider a new general integral operator, and we give sufficient conditions for the univalence of this integral operator in the open unit disk of the complex plane. Several consequences of the main results are also shown.